Applications of augmented reality in the neurosurgical operating room: A systematic review of the literature. (September 2021) - Chidambaram, Swathi; Stifano, Vito; Demetres, Michelle; Teyssandier, Mariano; Palumbo, Maria Chiara; Redaelli, Alberto; Olivi, Alessandro; Apuzzo, Michael L.J.; Pannullo, Susan C.
Highlights: Augmented Reality (AR) shows promise for future clinical use in neurosurgery. Several challenges exist in bringing AR into standard clinical neurosurgical practice. An exciting potential endures for combining AR with multimodal imaging techniques. Abstract: Advancements in imaging techniques are key forces of progress in neurosurgery. The importance of accurate visualization of intraoperative anatomy cannot be overemphasized and is commonly delivered through traditional neuronavigation. Augmented Reality (AR) technology has been tested and applied widely in various neurosurgical subspecialties in intraoperative, clinical use and shows promise for the future. This systematic review of the literature explores the ways in which AR technology has been successfully brought into the operating room (OR) and incorporated into clinical practice. A comprehensive literature search was performed in the following databases from inception-April 2020: Ovid MEDLINE, Ovid EMBASE, and The Cochrane Library. Studies retrieved were then screened for eligibility against predefined inclusion/exclusion criteria. A total of 54 articles were included in this systematic review. The studies were sub- grouped into brain and spine subspecialties and analyzed for their incorporation of AR in the neurosurgical clinical setting. AR technology has the potential to greatly enhance intraoperative visualization and guidance in neurosurgery beyond the traditional neuronavigation systems. However, there are several key challenges to scaling the use of this technology and bringing it into standard operative practice including accurate and efficient brain segmentation of magnetic resonance imaging (MRI) scans, accounting for brain shift, reducing coregistration errors, and improving the AR device hardware. There is also an exciting potential for future work combining AR with multimodal imaging techniques and artificial intelligence to further enhance its impact in neurosurgery.